Geometric Correlations Mitigate the Extreme Vulnerability of Multiplex Networks against Targeted Attacks - Kleineberg, Kaj-Kolja; Buzna, Lubos; Papadopoulos, Fragkiskos; Boguñá, Marián; Serrano, M. Ángeles (Physical review letters, 2017)
We show that real multiplex networks are unexpectedly robust against targeted attacks on high-degree nodes and that hidden interlayer geometric correlations predict this robustness. Without geometric correlations, multiplexes exhibit an abrupt breakdown of mutual connectivity, even with interlayer degree correlations. With geometric correlations, we instead observe a multistep cascading process leading into a continuous transition, which apparently becomes fully continuous in the thermodynamic limit. Our results are important for the design of efficient protection strategies and of robust interacting networks in many domains.